P93 Supporting Patient Involvement In Service Development: Eliciting Patient-centred Information To Inform Commissioning Of Copd Services. (10th November 2014) - Early, F; Watts, T; Homan, K; Green, A; Brookes, M; Fuld, J
Abstract : Introduction: Patient involvement in population level health care decisions often involves consultation rather than interactive decision-making. Lack of insight into appropriate methods is a barrier to patient involvement. Working Together for Change (WTfC) is a person-centred process to inform service development. Information from person-centred reviews (PCRs) is themed in a two-day co-production workshop. It is effective in social care and mental health but has not been applied in physical health. We tested its feasibility to improve the quality of person-centred information for COPD commissioners and of patient involvement. Methods: Forty COPD patients recruited from GP lists, secondary care and support groups participated in one-to-one PCRs. PCRs identified their priorities for what's working in their life regarding COPD, what's not working, what's important to the future. These patients, health service professionals and third sector organisations involved in COPD support were then invited to attend the two one-day workshops. Patients' priorities were themed collaboratively. Root cause analysis of what was not working was followed by statements of what success would look like if root causes were addressed. Action plans were created. Qualitative data from workshop observations and participant interviews were analysed using thematic analysis. Results: Service priorities included information, holistic care, access, dietary support, access to patient information for HCPs. The improved quality of the person-centred information was evident in the ways in which professionals' understanding of patient needs was enhanced through close, informal interaction with patients and carers, e.g. witnessing difficulties such as simultaneously eating and breathing and other physical limitations that prevent patients following healthcare advice (Table 1 ). Participation was positive for patients and professionals (Table 1 ) experiencing it as engaging and collaborative. Patients felt both heard and empowered and felt all the information they offered was precious. Discussion: Patients found it a powerful experience and felt they made a contribution for the future. Professionals gained emotional and practical insights which inspired motivation for change in service delivery. The process tapped into strong motivations for mutual understanding. It is an effective element in developing person-centred COPD services and is transferable to other LTCs. Supported by grant from the Health Foundation